Essential grammar in use : a self-study reference and practice book for elementary learners of English : with answers and eBook - Murphy, Raymond (Cambridge : Cambridge University Press, 2015)
The world's best-selling grammar series for learners of English. Essential Grammar in Use Fourth edition is a self-study reference and practice book for elementary-level learners (A1-B1), used by millions of people around the world. With clear examples and easy-to-follow exercises, it is perfect for independent study, covering all the areas of grammar you will need at this level. This edition includes an eBook which has the same grammar explanations and exercises found in the printed book, plus other great features. You can listen to all of the example sentences from the book, record your answers to exercises, highlight text, bookmark pages and add your own personal notes.
Supplementary exercises / Helen Naylor with Raymond Murphy.
Includes index.
Interactive eBook.
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc